Pengaruh Karakteristik Perusahaan, Kualitas Audit Terhadap Manajemen Laba : Kepemilikan Institusional Sebagai Moderasi - Anwar, Andrew; Rahayuningsih, Deasy Ariyanti (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2025)
The purpose of this research is to obtain empirical evidence that company characteristics, audit quality and institusional ownership as variable moderation have an influence on earnings management. The Company characteristics consists of leverage, profitability, firm size and company growth. This research used consumer cyclicals and consumer non-cyclicals company listed on the Indonesian Indonesian Stock Exchange from 2020 to 2022. The method is using purposive sampling with total of 171 data from 57 companies. This research used multiple regression and data were processed using Statistical Package for the Social Sciences (SPSS) program. The result of this research shows that leverage, firm size .company growth, institusional ownership and audit quality have no influence on earning management. The result also indicates that institusional ownership could not moderate the influence of leverage on earnings management. Other result such as profitability have influence on earnings management. The higher the profitability, company will do earnings management in order to make ROA more efficient in order to make investor more interest.